2007
DOI: 10.1158/1055-9965.epi-06-0767
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Variations in the Androgen and Estrogen Metabolic Pathways as Risk Factors for Sporadic and Familial Prostate Cancer

Abstract: Previous studies suggest that enzymes involved in the androgen metabolic pathway are susceptibility factors for prostate cancer. Estrogen metabolites functioning as genotoxins have also been proposed as risk factors. In this study, we systematically tested the hypothesis that common genetic variations for those enzymes involved in the androgen and estrogen metabolic pathways increase risk for sporadic and familial prostate cancer. From these two pathways, 46 polymorphisms (34 single nucleotide polymorphisms, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 51 publications
7
74
1
Order By: Relevance
“…Therefore, at least in the early stages of PC, 3b-Adiol formation may shift the equilibrium versus a slowing down of progression and invasiveness of the tumor cells. This exciting hypothesis has strong support in clinical observations, demonstrating that genetic alteration of several enzymes involved in androgenic steroid metabolism is linked to hereditary and sporadic PC susceptibility (Chang et al 2002, Steckelbroeck et al 2004, Bauman et al 2006, Cunningham et al 2007, Neslund-Dudas et al 2007, Park et al 2007, Ross et al 2008, Beuten et al 2009, Mindnich & Penning 2009). It has been established that enzyme responsible for 3b-Adiol formation from the DHT in prostate is AKR1C1; in fact, AKR1C1:AKR1C2 (responsible for 3a-diol formation from the DHT) transcript ratio fells in PC; thus, the data here presented provide clear explanations of these observations, since the reduction of 3b-Adiol levels in favor of 3a-Adiol may be a risk factor for PC in these patients, because the 3b-Adiol 'protective' effect will obviously disappear.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, at least in the early stages of PC, 3b-Adiol formation may shift the equilibrium versus a slowing down of progression and invasiveness of the tumor cells. This exciting hypothesis has strong support in clinical observations, demonstrating that genetic alteration of several enzymes involved in androgenic steroid metabolism is linked to hereditary and sporadic PC susceptibility (Chang et al 2002, Steckelbroeck et al 2004, Bauman et al 2006, Cunningham et al 2007, Neslund-Dudas et al 2007, Park et al 2007, Ross et al 2008, Beuten et al 2009, Mindnich & Penning 2009). It has been established that enzyme responsible for 3b-Adiol formation from the DHT in prostate is AKR1C1; in fact, AKR1C1:AKR1C2 (responsible for 3a-diol formation from the DHT) transcript ratio fells in PC; thus, the data here presented provide clear explanations of these observations, since the reduction of 3b-Adiol levels in favor of 3a-Adiol may be a risk factor for PC in these patients, because the 3b-Adiol 'protective' effect will obviously disappear.…”
Section: Discussionmentioning
confidence: 89%
“…However, the expression of all three genes has been measured in prostate cancer cell lines (Valentini et al, 2007). The association of the UGT2B15 D85Y polymorphism with prostate cancer has been examined with conflicting results (MacLeod et al, 2000;Gsur et al, 2002;Hajdinjak and Zagradisnik, 2004;Park et al, 2004;Cunningham et al, 2007). Similarly, numerous studies have explored the association of the UGT2B17 CNV and prostate cancer also with inconsistent conclusions (Park et al, 2006(Park et al, , 2007Gallagher et al, 2007;Karypidis et al, 2007;Olsson et al, 2008;Setlur et al, 2010).…”
mentioning
confidence: 99%
“…rs9340799 and the susceptibility of prostate cancer From the database search, we have identified ten studies that have reported the association of the variant of rs9340799 (XbaI, IVS1-351) and prostate cancer (Modugno et al, 2001;Suzuki et al, 2003;Fukatsu et al, 2004;Hernandez et al, 2006;Cunningham et al, 2007;Beuten et al, 2009;Gupta et al, 2010;Sissung et al, 2011;Szendroi et al, 2011;Safarinejad et al, 2012); however, one study reported by Hernandez et al (2006) had the same study population with the other study reported by Beuten et al (2009) and the it was excluded from our further study. In total, nine studies that have recruited a total of 2,792 prostate cancer patients and 3,397 controls with eleven individual study groups were included in the meta-analysis study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that rs9340799 may be a risk factor for prostate cancer and it may acts as a dominant model. rs2234693 and the susceptibility of prostate cancer In total, 17 individual studies were identified in the literature search stage that have evaluated the association between the rs2234693 and prostate cancer (Modugno et al, 2001;Suzuki et al, 2003;Tanaka et al, 2003;Fukatsu et al, 2004;Hernandez et al, 2006;Low et al, 2006;Berndt et al, 2007;Cunningham et al, 2007;Kjaergaard et al, 2007;Onsory et al, 2008;Sobti et al, 2008;Beuten et al, 2009;Gupta et al, 2010;Sonoda et al, 2010;Sissung et al, 2011;Szendroi et al, 2011;Safarinejad et al, 2012). Two of them were excluded for overlapping studied populations (Hernandez et al, 2006;Sobti et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation